An age-representative exploration of pro-social behavior: human generosity-offerings, expectations, and fairness - Szabo, Zoltan; Kovacs, Oliver Bela; Murai, Gabor; Voros, Zsofia; Kehl, Daniel (Marketing & Menedzsment, 2021)
THE AIM OF THE PAPER Fairness and other-regarding preferences arguably are defining factors of the experiments conducted with dictator games, which provide an opportunity to examine the components of pro-sociality. Our analysis focuses on the experimental results suggesting that offerings and expectations are based on egalitarian behavior. Besides that, we attempted to explore the age-specific characteristics of hypothetical dictator games. METHODOLOGY We used survey data of an age-representative sample to measure how the results support previous research findings stating that generosity and its age-related aspects play a crucial role in the formation of human decisions and expectations. MOST IMPORTANT RESULTS Our results confirmed the dominance of hyper-fair behavior. However, significant differences were found across the dictator game variants in terms of the amounts of money marked. Subjects in cases of charity-offering, recipient-offering, and expectation give lower amounts on average compared to recipient-offerings and fairness, respectively. In contrast, the marked amounts are higher for recipient-offerings than for expectations with the absence of any significant age-effect. Acknowledgements: The project was financed by the European Social Fund: Comprehensive Development for Implementing Smart Specialization Strategies at the University of Pecs (EFOP-3.6.1.- 16-2016-00004). Declarations of interest: none.